Acute Poisoning with Methadone (Dolphin) (Review) - Georgy A. Livanov; Alexander T. Loladze; Bair V. Batotsyrenov; Alexey N. Lodyagin; Sergey I. Glushkov; Tatiana V. Kharitonova; Alexandra A. Ivanova; Dmitry V. Baranov; Anna M. Antonova (Общая реаниматология)
Most publications report on the use of methadone as a medication, however an increase of the illegal use of methadone has been demonstrated worldwide over the recent years, thus increasing the number of hospitalizations due to acute poisoning with this synthetic opioid. The aim of the present review was to summarize current data on the mechanisms of toxicity, selective toxicity, toxicokinetics and toxicodynamics of methadone (Dolphin). The involvement of CNS, respiratory, cardiovascular and urinary systems in acute poisoning with methadone was dis- cussed. The practice of use of methadone in many countries as a medicine for the replacement therapy for opiate addicts was analyzed. In addition, it was suggested that the results of the use of naloxone antidote therapy in acute opioid poisoning do not always clearly demonstrate its sufficient efficacy. Ways to improve of the intensive therapy of severe acute poisoning by methadone were substantiated; in addition to general critical care methods, treatment with a complex metabolic antihypoxant cytoflavin should be considered.